The relational legacies of colonialism: peace education and reconciliation in Rwanda. Issue 5 (8th December 2020) - Schulz, Michael; Sentama, Ezechiel
Abstract: This article argues that decolonising educational undertakings is a difficult task, even when the ambitions to apply decolonising approaches are clearly articulated. Our case analysis of two contemporary master's in peace education programmes in Rwanda, that explicitly focus on reconciliation, shows evidence of limited capacity by the educators to decolonise them. We draw from semi-structured interviews with students and teachers, as well as text analysis of syllabuses, course guides, etc, and demonstrate that access for all societal groups to the programmes is restricted: the extent of decolonisation of the education itself, including alternative narratives of the conflict history as well as the conceptualisation of ethnic 'identity' within peace education, is still limited. These master of arts programmes thus preserve colonial legacies and contribute to maintain historical hierarchical relations between the Hutu and Tutsi groups in the country.